Taking Religion More Seriously: Beyond Secular Assumption in Studying Religion and Politics in Indonesia - Metera, Gde Dwitya Arief (Pusat Penelitian Politik, 2017)
AbstractÃ‚Â This review looks at two important recent publications by leading scholars on Indonesian politics namely Vedi HadizÃ¢â‚¬â„¢s Islamic Populism in Indonesia and the Middle East, and Michael BuehlerÃ¢â‚¬â„¢s The Politics of ShariÃ¢â‚¬â„¢a Law: Islamist Activists and the State in Democratizing Indonesia. Both publications have advanced the literature analytically by offering new approaches in a literature that is saturated by culturalist and, more recently, institutionalist arguments. BuehlerÃ¢â‚¬â„¢s book, however, is better-equipped in meeting the challenge offered by Benedict Anderson to understand the unique motive of religious politics in Indonesia than HadizÃ¢â‚¬â„¢s book. Buehler has managed to acknowledge the success of Islamist politics in Indonesia in asserting religious laws in the public sphere. Hadiz, by contrast, still treats the case of Indonesia as a case of failure of Islamist politics primarily by relying on the electoral performance of Islamist actors as an indicator. Ultimately, the two publications should be welcomed warmly by the student of religion and politics in Indonesia.Keywords: Islamist politics, Indonesian politics, Islamic populism, ShariÃ¢â‚¬â„¢a bylaws, Democratization.